Information Technology 's Role In Supply Chain Management - Wah, Poo Pek (2000)
Using Infineon Technologies ( Malaysia) Sdn Bhd. as a case, a study was conducted on the SCM in this company, on how Information Technology helps to optimise the value chain, and to have information collaborate with its trading partners.